1987
DOI: 10.1136/bmj.295.6596.473
|View full text |Cite
|
Sign up to set email alerts
|

Contamination by hepatitis B surface antigen in dental surgeries.

Abstract: 4 Ross GD, Thompson RA, Walport MJ, et al. Characterization of patients with an increased susceptibility to bacterial infections, and a genetic deficiency of leukocyte membrane complement receptor type 3 and the related membrane antigen LFA-1. Blood 1985;66:882-90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Among the environment isolates, one came from a headlight, one from an air/water syringe, two from high-speed drills and one from a low-speed drill. Although data on microbial contamination of surfaces or instruments from dental clinics are scarce, available research results have shown their extensive contamination by hepatitis B surface antigen (20) and hepatitis C virus (21); additional results have shown a high degree of contamination of trolley surfaces with Staphylococcus aureus and β haemolytic Streptococcus (16).…”
Section: Resultsmentioning
confidence: 99%
“…Among the environment isolates, one came from a headlight, one from an air/water syringe, two from high-speed drills and one from a low-speed drill. Although data on microbial contamination of surfaces or instruments from dental clinics are scarce, available research results have shown their extensive contamination by hepatitis B surface antigen (20) and hepatitis C virus (21); additional results have shown a high degree of contamination of trolley surfaces with Staphylococcus aureus and β haemolytic Streptococcus (16).…”
Section: Resultsmentioning
confidence: 99%
“…Some research has shown extensive contamination of surfaces and instruments in dental surgeries by hepatitis B surface antigen,22 and hepatitis C virus (HCV),23 but current publications do not contain any data on bacterial contamination.…”
mentioning
confidence: 99%
“…33 The HBV is capable of surviving on envi¬ ronmental surfaces for at least one week.333 In a recent study that sampled dental surgery environ¬ mental surfaces, HBsAg was found not only on surgical instruments, but also on dental chair head¬ rests, armrests, and surgeons' workbenches. 33 Many dermatologists perform a substantial num¬ ber of simple surgical procedures in patient exami¬ nation rooms apart from their designated minor surgery or procedure rooms. The physician and his or her staff should keep the above facts in mind when implementing measures of asepsis, decontamination, disinfection, and sterilization of instruments and environmental surfaces.…”
Section: Equipment Contamination and Instrument Sterilizationmentioning
confidence: 99%